Перiодичнi розв’язки систем нелiнiйних функцiональних рiвнянь - Пелюх, Г.П.; Сивак, О.А. (Нелінійні коливання, 2013)
Получены условия существования непрерывных T-периодических решений систем нелинейных функциональных уравнений и разработан метод их построения. For a system of nonlinear functional equations, we establish conditions for existence of continuous T-periodic solutions, and a method for their construction has been investigated.